Swine influenza: A disease of real concern - Nandi, S; Yadav, Jeet Singh (Indian Farming, 2015)
Swine influenza also known as swine flu, hog flu or pig flu is an infection in pigs caused by any one of several types of swine influenza virus. The subtypes of influenza A are H1N1, H1N2, H3Nl, H3N2 and H2N3. Swine influenza virus is common worldwide throughout pig populations. Transmission of the virus from pigs to humans is not common and does not always lead to human influenza. However, WHO on June 11, 2009 declared that current swineflu H1N1 disease has acquired pandemic status as it has spread throughout the world affecting millions of people in 206 countries globally causing 6,770 deaths from 526,060 cases officially upto 15th November 2009. As the disease is spreading rapidly from human to human, appropriate precautions should be taken to avoid being infected. If infection occurs one should follow strict isolation measure until healing of this disease and take proper treatment with informing the authority. As the influenza virus mutates at a very high rate close monitoring and surveillance of the disease in swine and humans should be carried out in collaboration with medical and veterinary professionals. However, the development of oseltamivir resistant influenza viruses have been reported and it may be a real concern until new effective drugs are developed in foreseeable future.